Traditional in Modern: The Existence of Village Governance Indonesia - Khairi, Halilul; Yahya, Afif Syarifudin; Alma'arif, Alma'arif; Kulachai, Waiphot; Nursyahidah Syed Annuar, Sharifah (Al-Risalah, 2025)
Villages existed before Indonesia became independent, with values that applied to its people. Modern government has organized villages into formal government institutions within the Indonesian government system, except for those that remain traditional villages. This study aims to analyze the value system of traditional villages in Indonesia and examine the structure of traditional village governance in the country. This study uses an interpretive paradigm with a qualitative approach. Data was collected qualitatively through interviews with several informants, including village heads, traditional leaders, community leaders, and local government officials. This study was conducted in three provinces with village characteristics that differ from those of other villages, namely North Sulawesi (Wanua), West Sumatra (Nagari), and Aceh (Gampong). The results gave rise to categories of villages that exist in Indonesia today, namely 1) Villages, but with Traditional Government; 2) Traditional Village, and its traditional government; 3) Village and its government; and 4) Traditional Village, but the government is the village. The contribution of this study is related to efforts to redefine Traditional Villages as they currently exist in Indonesia.